2015
DOI: 10.1007/s11695-015-1865-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bariatric Surgery in Type 2 Diabetes Mellitus Remission: the Role of Mini Gastric Bypass/One Anastomosis Gastric Bypass and Sleeve Gastrectomy at 1 Year of Follow-up. A European survey

Abstract: A significant BMI decrease and T2DM remission unrelated from weight loss were recorded for both procedures if compared to baseline values. At univariate and multivariate analyses, MGB/OAGB seems to outperform significantly SG. Four independent variables able to influence T2DM remission at 12 months have been identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 46 publications
(67 reference statements)
7
43
1
8
Order By: Relevance
“…Primary OAGB is effective in weight loss and remission of T2DM and superior to RYGB in this respect, while being associated with a shorter operating time and slightly less post-operative complications [35]. As a primary procedure when compared to RYGB, percentage excess weight loss (EWL) five years post-surgery of OAGB has been reported as 72.9% vs. 60.1% with a complication rate of 3.2% vs. 1.8% [36][37][38][39][40][41]. The prevalence of gastric ulcers between OAGB and RYGB is similar [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Primary OAGB is effective in weight loss and remission of T2DM and superior to RYGB in this respect, while being associated with a shorter operating time and slightly less post-operative complications [35]. As a primary procedure when compared to RYGB, percentage excess weight loss (EWL) five years post-surgery of OAGB has been reported as 72.9% vs. 60.1% with a complication rate of 3.2% vs. 1.8% [36][37][38][39][40][41]. The prevalence of gastric ulcers between OAGB and RYGB is similar [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…The patients who qualified for SG had a mean preopera- [24][25][26][27][28] Earlier studies have shown a marked improvement and normalization of parameters assessing diabetes control following bariatric treatment. 29,30 The present study assessed only SG and RYGB in this respect, because LAGB was used in only 1 patient with type 2 diabetes. A statistically significant reduction (p < 0.001) in insulin and HbA1c levels was noted at the 6-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes has resolved in 70-94% [22,60,61]. Kular found in diabetic patients with BMI <35 that HbA1c at 7 years after MGB was 5.7±1.8% [62]; earlier intervention resulted in higher remission rates.…”
Section: Comparison With Other Bariatric Operationsmentioning
confidence: 99%